Xây dựng nhật kí đọc sách giúp học sinh học đọc văn bản thơ mở rộng trong môn Ngữ văn 10 trung học phổ thông - Lưu Thị Trường Giang, Lưu Thị Trường Giang; Nguyễn Thị Quỳnh Mai, Nguyễn Thị Quỳnh Mai (Tạp chí Giáo dục, 2026)
In the current context of teaching Literature in high schools, guiding students to independently read additional poetic texts beyond the textbook plays a crucial role in developing reading and writing skills in line with the 2018 Literature curriculum. However, in reality, activities supporting students' understanding of expanded poetic texts still lack a systematic approach and do not truly facilitate students' proactive exploration, connection of knowledge, and development ofself-learning abilitiesin the context of digital transformation. Arising from this need, the project to develop a reading journal to help students learn to read expanded poetry texts in the 10th grade Literature subject (Textbook “Connecting Knowledge with Life”) was undertaken to design a tool to support students in note-taking, reflection, and connecting reading and writing according to the CIPO model, while still ensuring that the learning objectives of the 2018 Literature curriculum are met. Through the reading journal system, students not only practice reading comprehension skills specific to the poetry genre but also develop critical thinking, the ability to make connections and be creative in writing, thereby forming a habit of self-learning, enhancing proactiveness, and building a positive and effective learning environment.